About comunicación a distancia: dissemination of the mail art archive of the Vigo Experimental Art Centre - Galarza, Clarisa López (Universidad Nacional del Litoral, 2019)
This paper arises from a critical review of the first stage of the ordering and cataloging process of the mail art collection of the platense artist Edgardo Antonio Vigo. Through the notions of network, comunicación a distancia (long distance communication) and mail art, this work investigates conceptualizations and productions that displace and subvert the networks and circuits of art consumption of the s.XX, stressing its hegemonic circulation logic. Through the recovery of postal exchanges and strategies of comunicación a distancia which activated several international solidarity networks in contexts of social asphyxiation, censorship and repression, we will explore the potential of these strategies for the construction of emotional exchange and support spaces between members. In this sense, it focuses in the mail art as the implementation of a reciprocal postal support, which narrated the situation of its time with minimal latency.